in Probability recategorized by
450 views
2 votes
2 votes

If $A$ and $B$ are two related events, and $P(A \mid B)$ represents the conditional probability, Bayes’ theorem states that 

  1. $P(A\mid B) = \dfrac{P(A)}{P(B)} P(B\mid A)$
  2. $P(A\mid B) = P(A) P(B) P(B\mid A)$
  3. $P(A\mid B) = \dfrac{P(A)}{P(B)}$
  4. $P(A\mid B) = P(A)+P(B)$
in Probability recategorized by
450 views

1 Answer

1 vote
1 vote

Bayes’ theorem is stated mathematically as the following equation:

{\displaystyle P(A\mid B)={\frac {P(B\mid A)P(A)}{P(B)}}}

so option A is correct.

 

1 comment

Option A is correct.
0
0
Answer:

Related questions